2021
DOI: 10.21608/ejhm.2021.188554
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Outcome of Closure or Non-Closure of Peritoneum in Caesarian Section

Abstract: Background: Cesarean section (CS) can be considered as one of the most frequently performed surgical procedure worldwide, accounting for up to 70% of deliveries, depending on the facility being assessed and the country involved. In Egypt its rate reach about 51.8% from deliveries. Objetive: To compare closure versus non-closure of visceral and parietal peritoneum during primary cesarean section regarding early postoperative outcome. Patients and Methods: A randomized-controlled study that was conducted at Isma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This was also more cost-effective, since hospital stays for women with peritoneal non-closure were shorter and less suture material was used. In contrast, a recent study in 2021 (7), there was no SSD regarding the pain degree and the analgesia requirements. In a study in 2013 (11) due to adhesions caused by non-closure of the peritoneum during primary CS, the non-closure group had more postoperative discomfort.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This was also more cost-effective, since hospital stays for women with peritoneal non-closure were shorter and less suture material was used. In contrast, a recent study in 2021 (7), there was no SSD regarding the pain degree and the analgesia requirements. In a study in 2013 (11) due to adhesions caused by non-closure of the peritoneum during primary CS, the non-closure group had more postoperative discomfort.…”
Section: Discussionmentioning
confidence: 56%
“…Depending on the institution analyzed and the location involved, caesarean section (CS) is one of the most frequent surgical procedures performed worldwide, accounting for up to 70% of births. Approximately 5 to 20% of all births globally occur in underdeveloped countries (7) (8) revealed that the non-closure group had 6 minutes less operational time than the closure group, a study (3) stated a decrease in operational time (7.33 minutes) among women who had both peritoneal surfaces left unsutured as opposed to those who had their peritoneum sutured, a study (9) revealed that the operating time of the nonclosure group was shorter (11.2 minutes) than that of the closure group and in the study conducted in 2012 (5) the non-closure group had a shorter operating time (6.89 minutes) than the closure group. The mean of post-operative pulse was 97.69 ppm and mean of post-operative mean blood pressure was 90.48 mmHg while mean post-operative temperature was 37.33°C.…”
Section: Discussionmentioning
confidence: 99%